2021
DOI: 10.1093/hmg/ddab136
|View full text |Cite
|
Sign up to set email alerts
|

Systemic antisense therapeutics inhibiting DUX4 expression ameliorates FSHD-like pathology in an FSHD mouse model

Abstract: Aberrant expression of the double homeobox 4 (DUX4) gene in skeletal muscle causes muscle deterioration and weakness in Facioscapulohumeral Muscular Dystrophy (FSHD). Since the presence of a permissive pLAM1 polyadenylation signal is essential for stabilization of DUX4 mRNA and translation of DUX4 protein, disrupting the function of this structure can prevent expression of DUX4. We and others have shown promising results using antisense approaches to reduce DUX4 expression in vitro and in vivo following local … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 83 publications
0
34
0
Order By: Relevance
“… 29 , 30 , 31 For FSHD, no ASOs have yet been tested in patients; different studies, however, have shown that ASOs were efficient in reducing DUX4 and DUX4 target genes in FSHD myocytes and in FSHD mice. 15 , 16 , 17 , 18 , 19 , 21 A major advantage of our systemic approach compared to most other in vivo studies in FSHD mice is that all tested skeletal muscles were targeted by the ASO instead of one muscle or a part of the muscle. Next, this is the first ASO with cEt chemistry that has been tested for FSHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 , 30 , 31 For FSHD, no ASOs have yet been tested in patients; different studies, however, have shown that ASOs were efficient in reducing DUX4 and DUX4 target genes in FSHD myocytes and in FSHD mice. 15 , 16 , 17 , 18 , 19 , 21 A major advantage of our systemic approach compared to most other in vivo studies in FSHD mice is that all tested skeletal muscles were targeted by the ASO instead of one muscle or a part of the muscle. Next, this is the first ASO with cEt chemistry that has been tested for FSHD.…”
Section: Discussionmentioning
confidence: 99%
“…The ASO was able to reduce the DUX4 mRNA transcript, DUX4 target gene expression, and pathology in the tibialis anterior muscle. 21 …”
Section: Introductionmentioning
confidence: 99%
“…As potential therapies for FSHD, multiple groups are developing technologies to inhibit the function or expression of DUX4-FL (e.g. Bosnakovski et al, 2019 ; Bouwman et al, 2021 ; Das and Chadwick, 2021 ; Himeda et al, 2020 ; Lim et al, 2020 , 2021 ; Lu-Nguyen et al, 2021 ; Mariot et al, 2020 ; Mellion et al, 2021 ; Oliva et al, 2019 ; Rashnonejad et al, 2020 ; Šikrová et al, 2021 ). Direct targeting of DUX4 will likely be the primary therapeutic strategy for FSHD, because once begun, any technique that inhibits DUX4 expression or function should block multiple pathogenic changes that are dependent on DUX4 transcriptional activity ( Mitsuhashi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This treatment led to partial reductions in DUX4 and 2 DUX4-activated mouse target genes and partial improvement in histological and functional outcomes. This study is now published [ 19 ].…”
Section: Session 6: Antisense Strategiesmentioning
confidence: 99%